Geopolymer Concrete with Fly Ash - Lloyd, Natalie; Rangan, Vijaya (UWM Center for By-Products Utilization, 2010)
Geopolymer concrete results from the reaction of a source material that is rich in silica and alumina with alkaline liquid. A summary of extensive studies conducted on a fly ash-based geopolymer concrete is presented. Test data are used to identify the effects of salient factors that influence the properties of the geopolymer concrete and to propose a simple method for the design of geopolymer concrete mixtures. Test data of various short-term and long-term properties of the geopolymer concrete and the results of tests conducted on large-scale reinforced geopolymer concrete members show that geopolymer concrete is well-suited to manufacture precast concrete products that can be used in infrastructure developments. The paper also includes brief details of some recent applications of geopolymer concrete.